Developing views of proof of future primary school teachers - Samková, Libuše; Balko, Ludovít; Szarková, Dagmar; Tichá, Marie; Richtáriková, Dagmar (Slovak University of Technology in Bratislava, 2016)
In our contribution we focus on the possibility to develop views of proof of future primary school teachers during a university course on arithmetic conducted in inquiry-based manner. We present our classroom interventions aiming to route future primary school teachers towards secure methods of validation and non-empirical argumentation.
Rozvíjení pohledu na důkaz u budoucích učitelů 1. stupně ZŠ
Keywords: Future primary school teachers; inquiry-based mathematics education; secure methods of validation; non-empirical argumentation; proof; Budoucí učitelé 1. stupně ZŠ; badatelsky orientované vyučování matematice; bezpečné metody validace; deduktivní argumentace; důkaz